Transgene-free Genome Editing in Plants - Gu, Xiaoyong; Liu, Lijing; Zhang, Huawei (Frontiers in Genome Editing, 2021)
Genome editing is widely used across plant species to generate and study the impact of functional mutations in crop improvement. However, transgene integration in plant genomes raises important legislative concerns regarding genetically modified organisms. Several strategies have been developed to remove or prevent the integration of gene editor constructs, which can be divided into three major categories: 1) elimination of transgenic sequences via genetic segregation; 2) transient editor expression from DNA vectors; and 3) DNA-independent editor delivery, including RNA or preassembled Cas9 protein-gRNA ribonucleoproteins (RNPs). Here, we summarize the main strategies employed to date and discuss the advantages and disadvantages of using these different tools. We hope that our work can provide important information concerning the value of alternative genome editing strategies to advance crop breeding.